Dampak Liquidity dan Capital Intensity terhadap Tax Avoidance - Pingki Lutfiana Bella; Nera Marinda Machdar (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
Taxes is one of the main instruments in redistribution of wealth and the provision of public services. However, challenges such as tax avoidance, low compliance, and sometimes inefficient administrative systems are still problems faced. Recently, news about the phenomenon of tax avoidance has become a frequently discussed topic in various media. This research is intended for find and inspect the variables that impact Tax Avoidance. This research method uses a descriptive quantitative approach. The data used are figures obtained through previous research. The data collected from previous studies is secondary data which refers to processed data and investigated previously and has been created in document form. The sample determination method used in this research is purposive sampling. Based on research data, the results show that Liquidity and Capital Intensity have a significant positive effect on Tax Avoidance. These findings provide important insights for managers and policymakers about the importance of liquidity and capital capacity in tax avoidance strategies. These findings provide valuable insights for managers and policymakers regarding the importance of liquidity and capital capacity in developing tax reduction strategies.